The Use Google Classroom During Pandemic In Teaching Oral Descriptive Text of SMA Negeri 1 Peusangan Selatan - Khairul Mubarak; Iswadi, Iswadi (Journal of English Education and Social Science, 2024)
This research entitled is “The Use of Google Classroom During Pandemic In Teaching Oral Descriptive Text (a Collaborative Classroom Action Research at SMA Negeri 1 Peusangan Selatan)”. The researcher raised the problems of this research, namely: the first, How does the students improve their Oral Descriptive text through Google Classroom? And the second, How do students respond after using Google Classroom in Teaching Oral Descriptive text to the student at SMA 1 Peusangan Selatan?. The purpose of this study is to know the students improve their Oral Descriptive text through Google Classroom and to know the students respond after using Google Classroom in Teaching Oral Descriptive text to the student at SMA 1 Peusangan Selatan. The method used in this research is Collaborative Classroom Action Research. The researcher collaborated with teacher at SMA Negeri 1 Peusangan Selatan. The instruments used in this research are test, observation checklist and questionnaire. Based on the result of the data analysis, it can be found that, the mean score of the students test in oral descriptive text in first cycle was 36.55, in the second cycle was 67.75. based on the teaching and learning process the mean score of students’ observations in first cycle was 40.7 while in the second cycle was 82.1. the mean score of teacher observations in teaching oral descriptive text by using google classroom in first cycle was 56 while in the second cycle was 88. The students’ response to the application of the Google Classsroom in teaching oral descriptive text got an mean score of 87.11 or 3.33 (Strongly Agree). These results indicate that the use of google classroom in teaching oral descriptive text its good results and a satisfactory response. Thus this research is said to be successful.